Solar Thermal Cooling on the Northernmost Latitudes. (May 2015) - Shipkovs, Peteris; Snegirjovs, Andrejs; Shipkovs, Janis; Kashkarova, Galina; Lebedeva, Kristina; Migla, Lana
Abstract: The national priority axis is increase of renewables (RES) use in Latvian Energy sector; therefore, new solutions for Electricity, Heat and Cold production are sought for. Solar energy is available at the same time when there is need to cool rooms, so Solar Cooling systems are suitable also for Latvian conditions. In Latvia such systems are not used yet, so it is important to assess the potential of these systems. The sunlight duration and intensity depends on the season, weather conditions and geographical position of a country. As compared with the annual global solar radiation incident on horizontal surfaces in sunny regions (2200 kWh/m 2 ), in the northern Europe is half as much (1100 kWh/m 2 ). The solar energy potential defined for Latvia as technically achievable by 2020 is: for electricity 0.01 TWh and for heat 0.04 TWh. As shown by experimental studies, the application of solar collectors in Latvia can give good results. The energy of solar radiation can be employed for 1700-1900 hours annually. Due to a gradual increase in the comfort level, the demand for space cooling will grow in the near future. Solar cooling can be an alternative for electrically-powered compression-type chillers that currently are the most common in the Baltic States. The solar cooling system installed in the Institute of Physical Energetic is the first of the type in EU which is built at the latitudes higher than 55 degrees of north. Taking into account the fact that there were no systems plants of this type at so "cold" latitudes, first of all the models in PolySun were to be validated, and a dynamic simulation program containing the five-years meteorological data was to be developed. The solar cooling system has been optimized using multiple simulations. The influence of the system's different elements on its operation is evaluated. The optimal model developed for the given climatic conditions is described.